Upaya Mengatasi Kesulitan Membaca di Kelas 1 MI Ma’arif Soka Poncowarno Melalui Metode Struktural Analitik Sintetik - Rosadah, Zaenur; Ratri, Rose Kusumaning (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
Reading difficulties are a common problem that often occurs in lower class students. This research aims to find out how teachers try to overcome reading difficulties in class 1 MI Ma'arif Soka Poncowarno through synthetic analytical structural methods. This research uses a qualitative approach by processing data from field research. Data collection techniques use observation, interviews, and documentation which are then analyzed using data reduction, data presentation, and drawing conclusions. The instrument used is an interview guide to determine the extent of students' reading abilities and efforts to overcome reading difficulties using synthetic analytical structural methods. The research results showed that there were efforts by teachers to overcome students' reading difficulties using synthetic analytical structural methods, especially in Indonesian language learning, including planning, implementation and evaluation activities. Implementation activities include preliminary, core and closing activities. Based on the research results, it can be concluded that the synthetic analytical structural method has been implemented as well as possible, but the steps of the synthetic analytical structural method have not been fully described, which includes three stages, namely the planning, implementation and evaluation stages.